46. Tacrolimus Increases Susceptibility to Secondary Infection in a Mouse Model. (31st December 2020) - Miller-Handley, Hilary; Kinder, Jeremy; Pham, Giang; Way, Sing Sing
Abstract: Background: Transplant acceptance requires life-long pharmacological intervention that broadly suppresses recipients' immunity in order to prevent rejection of foreign graft. In turn, non-specific immune-suppression in these patients is also associated with increased risk of infection from opportunistic pathogens. Currently our knowledge on the effects immune suppressive therapies on adaptive immune components response in patients is limited Methods: To investigate this we established a mouse model of post-transplant immune suppression therapy, using tacrolimus. To dissect the effects of tacrolimus on infection susceptibility, tacrolimus-treated mice were infected with a virulent strain of recombinant Listeria monocytogenes (Lm) expressing model antigens. Infection with this transgenic strain of Lm transforms these model antigens into surrogate Lm antigens and allows tracking of pathogen-specific T-cells using MHC tetramer staining. Results: Here we show, tacrolimus treatment triggered increased susceptibility to secondary, but not primary Lm infection with increased bacterial burden in the liver and spleen tissues. Increased susceptibility during secondary infection paralleled dampened functional activation of Lm-specific CD8+ T cells as indicated by diminished in vivo cytolytic activity. Interestingly, when tacrolimus treatment was initiated only during primary or during secondary infection susceptibility to infection was overturned as both groups of mice had lower bacterial burden in target tissues. This suggests that while tacrolimus treatment does not negatively impact primary immune response, it may dampen the formation of CD8+ T cell memory. Conclusion: Further studies will investigate the long-term durability of blunted pathogen-specific memory and CTL activity triggered by tacrolimus treatment after cessation of therapy. These findings will allow more defined prediction of patient risk of infection allowing for a personalized prophylaxis regimen. Disclosures: All Authors : No reported disclosures